ISLAMIC LEGAL REFORM BASED ON MAQĀṢID SYARĪ‘AH: A STUDY OF AL-GHAZĀLĪ’S THOUGHTS AND ITS RELEVANCE IN THE CONTEXT OF INDONESIAN FAMILY LAW - Majid, Abdul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This article examines the renewal of Islamic law based on maqāṣid al-syarī‘ah in al-Ghazālī's thinking and its relevance to Islamic family law in Indonesia. In al-Mustaṣfā, al-Ghazālī emphasizes the five main goals of the Shari'a: protecting religion, soul, reason, offspring, and property. However, regulations such as Law no. 1 of 1974 and the Compilation of Islamic Law (KHI) still rely on classical jurisprudence which is not yet fully adaptive to social change. This research uses a normative-philosophical approach with literature study to explore how the concept of maqāṣid can be the basis for family law reform. The results of the study show that maqāṣid in al-Ghazālī's framework provides direction for reforming family law on issues of gender justice, children's rights, unilateral divorce, and marriage age limits. This approach emphasizes the importance of the substance of benefits in establishing law, not just the textuality of the arguments. Thus, maqāṣid becomes a strategic foundation in building Islamic family law in Indonesia that is more responsive, fair and contextual.